Catalytic pyrolysis of wheat bran for hydrocarbons production in the presence of zeolites and noble-metals by using TGA-FTIR method. (May 2016) - Lazdovica, K.; Liepina, L.; Kampars, V.
Highlights: All investigated catalysts decreased formation of volatile matter and increased solid residue of wheat bran pyrolysis. All catalysts showed deoxygenation activity. Noble-metal catalysts promoted formation of aromatics whereas zeolites advanced formation of aliphatics and olefins. Abstract: Pyrolysis of wheat bran with or without catalysts was investigated using TGA-FTIR method in order to determine the influence of zeolite and noble metal catalysts on the evolution profile and relative yield of the volatile compounds. The addition of all catalysts decreased the volatile matter of wheat bran from 76.3% to 75.9%, 73.9%, 73.5%, 69.7% and increased the solid residue from 18.0% to 18.4%, 20.4%, 20.8%, 24.6% under the catalyst of ZSM-5, 5% Pd/C, MCM-41, and 5% Pt/C. Noble-metal catalysts had higher activity for deoxygenation of compounds containing carbonyl, carboxyl, and hydroxyl groups than zeolites. Degradation of nitrogen containing compounds atom proceeded better in presence of zeolites. Noble-metal catalysts promoted formation of aromatics and changed the profiles of evolved compounds whereas zeolites advanced formation of aliphatics and olefins.